Association of TLR-4 regulatory variants (rs41426344 and rs7873784) with rheumatoid arthritis in a Chinese population. (August 2016) - Guo, Xiang-hua; Shao, Li; Li, Jian; Mao, Yu-jing; Zhang, Li-li; Song, Qin
Toll-like receptors (TLRs) play a key role in both innate and adaptive immunity. The role of TLR-4 in various autoimmune disorders has been well documented. Variations in the TLR-4 gene have been linked with susceptibility to rheumatoid arthritis (RA). In the present report, we conducted a hospital-based case-control study to investigate whether common polymorphisms in the TLR-4 gene are associated with susceptibility/resistance to development of RA in a Chinese population. A total of six single nucleotide polymorphisms (Asp299Gly, Thr399Ile, rs10759932, rs41426344, rs11536889, and rs7873784) were genotyped by PCR-RFLP in 250 RA patients and 248 healthy controls. Distribution of genotypes and alleles in RA and controls were compared by Fisher's exact test. The prevalence of minor allele, heterozygous and homozygous mutants for rs41426344 polymorphism were more frequent in RA patients compared to healthy controls (C: P <0.0001, OR = 5.51 [3.37–8.99]; GC: P <0.0001, OR = 7.38 [4.10–13.29]; CC: P = 0.01, OR = 4.73 [1.28–17.47]). Similarly, the frequencies of CC genotype and C allele of rs7873784 polymorphism were significantly higher in RA than healthy controls ([GC: P = 0.008, OR = 1.77 [1.16–2.70]; C: P = 0.01, OR = 1.61 (1.11–2.34]). However, genotypes and alleles distribution of rs10759932 and rs11536889 were comparable in both clinical categories. Similar to earlier observations, all participants were wild type for TLR-4 codon polymorphisms (Asp299Gly and Thr399Ile). In conclusion, TLR-4 (rs41426344 and rs7873784) variants are associated with susceptibility to development of RA in a Chinese population.